The Interface Between Metacognitive Strategy Training and Locus of Control in Developing EFL Learners’ Listening Comprehension Skill - Taherkhani, Bahador; Aliasin, Seyed Hesamuddin; Khosravi, Robab; Izadpanah, Siros (Frontiers in Education, 2022)
This study investigated the effects of metacognitive listening strategy instruction and learners' locus of control orientation on the listening comprehension of EFL learners. 100 EFL students at the University of Zanjan and Imam Khomeini International University of Qazvin were randomly chosen. The participants were randomly assigned to an experimental group (N=50) and a control group (N=50). The experimental group received 10 weeks of treatment including 10 sessions of metacognitive listening strategy training. Both groups took the Metacognitive Awareness Listening Questionnaire and Rotter's Internal-External Locus of Control Scale prior to the treatment sessions. Then, they had a listening pre-test and after treatment, the listening post-test was administered and the required data was obtained. The findings revealed that metacognitive listening strategy instruction had a significant impact on the learners' listening comprehension in general and for the learners with internal LoC in particular; Furthermore, internal LoC turned out to be a predictor of better listening comprehension. In addition, it was found that male internalizers outperformed their female counterparts.